A method of characterising the complex anatomy of vascular occlusions and 3D printing biomimetic analogues. Issue 1 (7th March 2022) - O'Reilly, Muireann; Beatty, Rachel; McBride, Shauna; Brennan, Benjamin; Dockery, Peter; Duffy, Garry P.
Abstract: Chronic total occlusions (CTOs) occur in approximately 40% of individuals with symptomatic peripheral arterial disease and are indicative of critical limb ischaemia. Currently, few medical devices can effectively treat CTOs long‐term, with amputation often required. This is due to a lack of knowledge of CTO anatomy, making device design and testing difficult. This study is a proof‐of‐concept study, which aimed to develop a workflow for further characterising the complex multi‐material anatomy of CTOs and creating 3D models of CTO components, which may be useful in producing a vascular CTO biomimetic for device testing. Here, we establish such a workflow using samples of atheromatous plaques. We focus on a high‐resolution, non‐destructive microcomputed tomography (μCT) technique which enables visualisation of occlusion anatomy at a greater resolution than computed tomography angiography (CTA), which is the typical modality used for CTO clinical visualisation. Four arteries ( n = 2 superficial femoral; n = 2 popliteal) with evidence of atheromatous plaques were cut into 8 cm segments, which were then stained with iodine and scanned at low resolution, with calcified regions rescanned at high resolution. Resulting files were manually segmented to generate 3D models, which were then 3D printed in resin using a stereolithography printer to produce parts suitable for creating a biomimetic. In total, μCT files from three arterial segments ( n = 2 high resolution, n = 1 low resolution) were deemed suitably calcified for segmentation, and thus were segmented to produce 3D models. 3D models of the arterial wall, intima and atheromatous calcium deposits from a high‐resolution popliteal artery scan were successfully 3D printed at several scales. While this research is at an early stage, it holds great promise. The workflow for segmentation and 3D printing various components of an atheromatous plaque established here is replicable and uses software and equipment which are accessible to research laboratories in both academia and industry. The ability to print detailed models on a desktop 3D printer is unprecedented and can be improved further, which is promising for future development of biomimetics with multi‐material detail of both soft tissue and calcified components of a vascular occlusion. Indeed, this workflow provides a solid foundation for future studies of CTO anatomy and the creation of true, multi‐material CTO biomimetics. Such biomimetics may enable the development of improved interventional devices, as they would mimic the general in vivo CTO environment. As this method cannot be applied in vivo, we cannot yet produce patient‐specific biomimetics, however, these analogues would still be important in device development, which would improve patient outcomes in critical limb ischaemia. Abstract : We have described a microcomputed tomography method which provides multi‐material detail on the calcified and soft tissue components of vascular occlusions. This is enables models of various components of the occlusion to be 3D printed, for use in the creation of biomimetic analogues. Having this detail on occlusion anatomy is important for the development and testing of interventional medical devices, particularly for treatment of chronic total occlusions.